The role of activists in access to HIV and tuberculosis treatment and prevention. Issue 4 (July 2017) - Geffen, Nathan
Abstract : Purpose of review: We describe the role of activism in improving access to quality HIV treatment. Recent findings: In many countries, AIDS activists have campaigned for improved access to HIV treatment and prevention interventions. Studying medicine, epidemiology and law, and developing expertise in these fields, has been crucial to the success of these campaigns. Also important has been the building of alliances by activists with clinicians, nurses, scientists, and public health policy experts, persuading them of the importance of these campaigns. This article describes examples of campaigns in several middle and low-income countries, showing how activists, by becoming familiar with HIV science, have helped make antiretrovirals available to millions of people across the world. HIV activists have also been drawn into, and driven, broader struggles for health social justice, such as campaigns for new tuberculosis and hepatitis C. Summary: Scientists and activists need to continue to work together to improve access to treatment. But to be effective, a critical mass of activists must develop expertise in HIV science and the law.